A new technique for reduction of scattered Gamma photons in Tc-99m SPECT imaging - Sayed, Inayatullah Shah; Zakaria, Ahmad; Haque, Tuhin (2011)

(untitled)
In healthcare, the prime objective prior to cure any disease is accurate diagnosis of abnormalities in humane. There are different diagnostic procedures and techniques. In this regard, imaging techniques play a potential role. Single Photon Emission Computed Tomography (SPECT) imaging is one among them. The technique uses some gamma photon emitting radionuclides and it is applied worldwide as an important diagnostic imaging tool. However, the technique has some limitations, e.g., equipment related, absorption and scattering of gamma photons within the patient body. Scattering of gamma photons degrade the system spatial resolution. Consequently, image quality is degraded and quantitative accuracy of radioactivity distribution is limited. This work attempts to reduce the effects of scattered gamma photons from SPECT images. There are some scatter correction techniques and each technique has limitations in one or another way. A unique technique has been introduced to absorb some fraction of scattered gamma photons from the image raw data before their registration. The technique uses thin sheets of materials; copper and aluminum as physical filters. SPECT data are acquired by using Toshiba GCA 901 A/HG gamma camera. Carlson’s phantom filled with water is used. Cold and hot regions inserts are placed in the phantom. Tc-99m radionuclide is uniformly distributed in the phantom. Either LEGP or LEHR collimators are used. Data acquisition parameters are chosen as those are selected for patient studies. Data are acquired with and without physical filters. Images are reconstructed by FBP reconstruction technique with Butterworth filter. Chang’s attenuation correction technique is applied for compensation of absorption of gamma photons. Images obtained with and without physical filtered data are analyzed and compared in terms of perceived image quality, hot and cold region detectability and image contrast. Results show that, perceived image quality, hot and cold region detectability and image contrast is improved when physical filters are used. This suggests that the technique may have potential applications in clinical studies.